Symptoms of anxiety and depression in children with developmental coordination disorder: a systematic review - Tatiane Targino Gomes Draghi; Jorge Lopes Cavalcante Neto; Liz Araújo Rohr; Lemke Dorothee Jelsma; Eloisa Tudella (Brazilian Society of Pediatrics, 2020)
Objective: To find evidence of the symptoms of anxiety/depression in children with developmental coordination disorder as compared to their typically developing peers at both the group and individual level, and to identify how many different tools are used to measure anxiety and/or depression. Methods: Electronic searches in eight databases (PubMed/MEDLINE, Scopus, Web of Science, ERIC, PsycINFO, Embase, SciELO and LILACS), using the following keywords: 'Developmental Coordination Disorder,' 'Behavioral Problems,' 'Child,' 'Anxiety,' 'Depression,' 'Mental Health,' and 'Mental Disorders.' The methodological quality was assessed by Newcastle‐Ottawa Scale adapted for cross‐sectional studies and the NOS for cohort studies. The studies were classified as low, moderate, or high quality. To provide clinical evidence, the effect size of the symptoms of anxiety and depression was calculated for each study. Results: The initial database searches identified 581 studies, and after the eligibility criteria were applied, six studies were included in the review. All studies were classified as being of moderate to high quality, and the effect sizes for both anxiety and depression outcomes were medium. The evidence indicated that all of the assessed studies presented more symptoms of anxiety and depression in children with developmental coordination disorder than in their typically developing peers. On the individual level, this review found children with clinical symptoms of anxiety in 17-34% (developmental coordination disorder) and 0-23% (typically developing), and of depression in 9-15% (developmental coordination disorder) and 2-5% (typically developing) of the children. Conclusions: Children with developmental coordination disorder are at higher risk of developing symptoms of anxiety and depression than their typically developing peers. Resumo: Objetivo: Encontrar evidências dos sintomas de ansiedade/depressão em crianças com transtorno do desenvolvimento da coordenação em comparação com seus pares com desenvolvimento típico, a nível individual bem como em grupo, e identificar quantas ferramentas diferentes são utilizadas para medir a ansiedade e/ou depressão. Métodos: Pesquisa eletrônica em oito bases de dados (PubMed/Medline, Scopus, Web of Science, Eric, PsycINFO, Embase, Scielo e Lilacs), utilizando as seguintes palavras‐chave: 'Developmental Coordination Disorder', 'Behavioral Problems', 'Child', 'Anxiety', 'Depression', 'Mental Health' e 'Mental Disorders'. A qualidade metodológica foi avaliada pela escala de Newcastle‐Ottawa (NOS) adaptada para estudos transversais e pela escala de Newcastle‐Ottawa (NOS) para estudos de coorte. Os estudos foram classificados em: qualidade baixa, moderada e alta. Para fornecer evidência clínica, o tamanho do efeito dos sintomas de ansiedade e depressão foi calculado para cada estudo. Resultados: As buscas iniciais nas bases de dados identificaram 581 estudos e, após a aplicação dos critérios de elegibilidade, seis estudos foram incluídos na revisão. Todos os estudos foram classificados como tendo qualidade moderada a alta e os tamanhos do efeito para os desfechos de ansiedade e depressão foram médios. As evidências indicaram que 100% dos estudos avaliados apresentaram mais sintomas de ansiedade e depressão em crianças com transtorno do desenvolvimento da coordenação do que em seus pares com desenvolvimento típico. No nível individual, encontramos crianças com sintomas clínicos de ansiedade em 17‐34% (transtorno do desenvolvimento da coordenação) e 0‐23% (desenvolvimento típico) e de depressão em 9‐15% (transtorno do desenvolvimento da coordenação) e 2‐5% (desenvolvimento típico) das crianças. Conclusões: Crianças com transtorno do desenvolvimento da coordenação apresentam maior risco de desenvolver sintomas de ansiedade e depressão do que seus pares com desenvolvimento típico. Keywords: Developmental coordination disorder, Emotional health, Mental health, Anxiety, Depression, Palavras‐chave: Transtorno do desenvolvimento da coordenação, Saúde emocional, Saúde mental, Ansiedade, Depressão